Solution-phase phosphorus substitution for enhanced oxygen evolution reaction in Cu2WS4. Issue 1 (2nd January 2019) - Novak, Travis G.; Prakash, Om; Tiwari, Anand P.; Jeon, Seokwoo
Abstract : Solution-phase synthesis of a transition metal phosphide for use as a highly efficient electrocatalyst. Abstract : Transition metal phosphides are among the most promising materials for achieving efficient electrocatalytic performance without the use of rare or expensive noble metals. However, previous research into phosphides for the hydrogen evolution reaction (HER) or oxygen evolution reaction (OER) has focused on high-temperature vapor-phase processes, which are not practical for large-scale applications. Here, we introduce a simple, one-step solution-phase method of phosphide synthesis by modifying Cu2 WS4 using triphenylphosphine (TPP), which serves to substitute S with P and transform the normally inactive basal plane of Cu2 WS4 into a defect-rich, activated basal plane. The OER activity was significantly enhanced by phosphorus substitution, with the resulting Tafel slope of the sample with ∼8 at% phosphorus reaching 194 mV dec −1, a result close to that of the best OER catalyst (RuO2, 151 mV dec −1 ). The sample possessed stable OER performance, showing no degradation in current density over ∼24 hours (500 cycles), proving the robust and stable nature of the phosphorus substitution. These results open the possibility for further phosphide catalyst development using this low-cost, solution-phase method.